2023
DOI: 10.1039/d3gc01927f
|View full text |Cite
|
Sign up to set email alerts
|

Green mechanochemical synthesis of imine-linked covalent organic frameworks for high iodine capture

Normanda Brown,
Ziad Alsudairy,
Ranjan Behera
et al.

Abstract: Covalent organic frameworks (COFs) have emerged as promising adsorbents for radioiodine capture. However, the conventional solvothermal synthesis contradicts the principles of green chemistry due to the use of hazardous solvents,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…It has been shown in the literature that the pore volume of the framework material determines the iodine capture capacity of COF materials. The COF isomers we obtained not only have different crystal structures but also have very different conjugated structures, pore environments, and pore sizes. Surprisingly, after the iodine capture experiment, it is not difficult to see that whether it is AA-stacked TAPT-TFPA COF, inclined-stacked TAPT-TFPA COF, or TAPA-TFPT COF, they show basically the same iodine capture ability.…”
Section: Resultsmentioning
confidence: 85%
“…It has been shown in the literature that the pore volume of the framework material determines the iodine capture capacity of COF materials. The COF isomers we obtained not only have different crystal structures but also have very different conjugated structures, pore environments, and pore sizes. Surprisingly, after the iodine capture experiment, it is not difficult to see that whether it is AA-stacked TAPT-TFPA COF, inclined-stacked TAPT-TFPA COF, or TAPA-TFPT COF, they show basically the same iodine capture ability.…”
Section: Resultsmentioning
confidence: 85%
“…It is worth noting that most CM-COFs exhibit the same topological structure and layer stacking mode as the corresponding achiral COFs synthesized directly from 1,3,5-triformylbenzene and amino monomers, except for CM-COF-2. Previous reports have shown that an AA-stacking COF could be obtained through the direct condensation between 1,3,5-triformylbenzene and 2,5-dimethyl-1,4-benzenediamine, 37 which differs from the ABC-stacking structure observed in CM-COF-2. To investigate the difference between traditional solvothermal synthesis and the cage-to-COF process, reaction time-dependent FT-IR and PXRD measurements were conducted (Figure S8).…”
Section: ■ Introductionmentioning
confidence: 90%
“…1,2 Nuclear power has contributed approximately 11% of the total electricity in the world, and the proportion is still increasing fast with the explosively rapid development of contemporary industries and the global energy shortage. 3 However, the associated radioactive nuclear wastes have brought severe threats to the environmental system, which are of high priority to deal with for sustainable development and public acceptance of nuclear energy. 4,5…”
Section: Introductionmentioning
confidence: 99%